The Silent Language of Political Communication of President Vladimir Putin - Rustanta, Agustinus; Oetomo, Koesmaryanto; Gultom, Karin; Alfani, Hendra (KnE Social Sciences, 2023)
The delivery of messages in political communication varies. One of them was President Vladimir Putin’s political communication when he received a diplomatic visit from other Presidents, including President Joko Widodo’s visit in 2022. The messages sent and received by these two important people provoked different perceptions by the public. The extreme social distancing between President Vladimir Putin and other Heads of State was interesting to analyze. The purpose of this study was to analyze the distance (proxemics) of communication of President Vladimir Putin and President Joko Widodo, and President Vladimir Putin and President Emmanuel Macron. Data were collected from newspapers. Photographs showing the communication distance between President Putin and other heads of state were analyzed using proxemic theory. This research shows that President Vladimir Putin has a different way of welcoming and engaging himself when communicating with the President of Indonesia and the President of France. This non-verbal way of conveying messages shows both power and respect for the interlocutor. Keywords: communication, proxemic, symbol, non-verbal communication